Can Aristotle’s Phronimos return? The revival of interest in Aristotle’s phronesis in political philosophy/theory - Faure, Murray (Acta Academica: Critical views on society, culture and politics, 2013)
This article explores the contemporary revival of interest in Aristotle’s notion of phronesis, practical wisdom. It commences by analysing this ancient intellectual virtue, its relation to Aristotle’s moral virtues and the role that philosophy occupies in his understanding of political science and the nature of politics. Following this, the factors, both practical and theoretical, that account for efforts to reincarnate the Phronimos (the man of practical wisdom) in our time is examined. The analysis subsequently identifies transhistoricist political theory which, unlike other forms of theorising, explicitly sets itself the goal to recover from the past an understanding of phronesis and instances of practical wisdom that can potentially be of use in contemporary times. In closing, some of the cognitive, political and practical obstacles that must be bypassed for political philosophy/theory to realise such a goal is explored and appraised.